2018
DOI: 10.1002/dev.21628
|View full text |Cite
|
Sign up to set email alerts
|

Rapid plasticity attenuation soon after birth revealed by habituation in newborn chicks

Abstract: Habituation reflects a form of experience-dependent plasticity whereby the organism progressively learns to ignore the irrelevant information repeatedly encountered. Here, we measured the freezing response to a repeated loud noise in three groups of newborn chicks (Gallus gallus) of different ages (1-2 Day old, 2-3 Day old, and 3-4 Day old) to investigate the ontogeny of habituation in this avian species. Habituation was already present 1 Day after hatching, revealing that the neural mechanisms underlying this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…This rapid attenuation of plasticity could partly explain the benefits of precocious learning, since it is well known that to acquire full proficiency in some activities, practice should start at an early age during childhood. In avian species, this massive learning capacity is restricted to a narrow time window soon after birth, showing that younger individuals may learn more than their 1-day-older companions (Chiandetti, Dissegna, & Turatto, 2018). Bateson (1964b) found that while chicks approached a novel object on the first day after hatching, on the following 4 days, the majority progressively increased the avoidance of the same object.…”
Section: Extraordinary Precocious Learners Too?mentioning
confidence: 99%
“…This rapid attenuation of plasticity could partly explain the benefits of precocious learning, since it is well known that to acquire full proficiency in some activities, practice should start at an early age during childhood. In avian species, this massive learning capacity is restricted to a narrow time window soon after birth, showing that younger individuals may learn more than their 1-day-older companions (Chiandetti, Dissegna, & Turatto, 2018). Bateson (1964b) found that while chicks approached a novel object on the first day after hatching, on the following 4 days, the majority progressively increased the avoidance of the same object.…”
Section: Extraordinary Precocious Learners Too?mentioning
confidence: 99%
“…However, little is known about habituation in Coleoptera, the order of insects that contains the most species compared to any other in the animal kingdom. Some studies have shown that habituation occurs in different species from the first moments of life (e.g., Carew, 1987, 1988;Chiandetti et al, 2018). Furthermore, habituation has been reported even in embryonic stages of domestic chicks (Turatto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, we explored habituation and dishabituation of the defensive (freezing) response induced by a sudden acoustic stimulation during the early stages of development of a precocial avian species, the chick ( Gallus gallus ). We have already shown that in this species habituation is fully present in the first days after hatching (Chiandetti, Dissegna, & Turatto, 2018; Chiandetti & Turatto, 2017), and by adapting the same paradigm, here we tested whether dishabituation is also present soon after birth (i.e., in 1-day-old chicks) or, alternatively, whether it emerges later during the chick’s ontogenesis (i.e., in 3-day-old chicks).…”
mentioning
confidence: 99%